Environmental Change, Human Resources and Organizational Turnaround - Boyne, George A.; Meier, Kenneth J. (Journal of Management Studies, 2009)
abstractResearch on turnaround has largely focused on the impact of retrenchment and repositioning, and has paid less attention to the impact of changes in the task environment and human resources on recovery from decline. Moreover, all of the empirical research on turnaround has been conducted on private organizations. We develop a new model that is derived from theories of environmental and human resource effects on organizational performance. We apply this model to failing school districts in Texas, and find that turnaround is influenced by changes in the munificence and complexity of task environments, and the appointment of a new chief executive and front‐line staff.